Judgesâ Legal Reasoning on Child Protection: Analysis of Religious Courtsâ Decisions on the Case of Child Parentage - Wahyudi, Muhamad Isna (Al-Jamiah: Journal of Islamic Studies, 2017)
This paper examines four religious courtsâ decisions on child legal status, especially child parentage, after Constitutional Courtâs decision on the legal status of child born out of wedlock. The Constitutional Courtâs decision has triggered controversy on the rights of child born out of wedlock due to lack of explanation concerning term âcivil legal relationship with the biological fatherâ. To study the decisions, the author uses legal philosophy approach, both in legal science and Islamic law, focused on legal reasoning used by judges in decisions on child parentage. As the result, the author finds two types of legal reasoning employed by judges of religious courtsÂ  in dealing with cases of child parentage, doctrinal-deductive legal reasoning and maá¹£laá¸¥a based legal reasoning. It argues that the employment of doctrinal-deductive legal reasoning by the judges has not benefitted children and therefore the protection of childâs rights has not been optimally made nd that the employment of maá¹£laá¸¥a based legal reasoning by the judges has led to the better protection of childâs rights.[Tulisan ini membahas empat putusan pengadilan agama terkait status hukum anak, khususnya waris anak, setelah dikeluarkannya putusan Mahkamah Konstitusi (MK) tentang status hukum anak di luar nikah. Putusan MK telah memicu kontroversi karena kesenjangan penjelasan tentang adanya hak perdata seorang anak yang lahir di luar nikah dengan ayah biologisnya. Dalam mengkaji persoalan ini, penulis menggunakan pendekatan filsafat hukum, baik secara ilmiah atau hukum Islam, yang fokus pada argumentasi hukum para hakim dalam kasus hak waris anak. Penulis setidaknya menemukan dua tipe argumentasi yang digunakan para hakim dalam kasus tersebut, yaitu: alasan hukum legal deduktif-doktrinal dan alasan hukum berbasis maá¹£laá¸¥ah. Tipe yang pertama cenderung melemahkan perlindungan hak anak, sedangkan tipe kedua justru akan menguatkan hak anak.]